Sustaining Physical Literacy Through Microlearning: The Curation, Transformation, and User Acceptability of TeachTok for Grade 5 Fitness During Climate-Induced Class Suspensions - Tipay, Daniel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated TeachTok as a teacher-curated, curriculum-aligned, and safety-conscious Alternative Delivery Mode (ADM) for Grade 5 Physical Fitness during climate-related class suspensions. Anchored on Connectivism, Self-Determination Theory, the Technological Pedagogical Content Knowledge (TPACK) framework, and the Technology Acceptance Model (TAM), the study employed a multi-phase Educational Design and Development Research (DDR) Type 1 using a sequential exploratory mixed methods design. Data were collected through a PRISMA-guided systematic literature review, semi-structured interviews, focus group discussions, expert validation, and a learner acceptability survey involving 37 Grade 5 learners, 10 interview participants, 10 focus group discussion participants, and three expert validators. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using descriptive statistics through weighted means. Findings showed that the redesign of TeachTok was guided by evidence-based microlearning principles emphasizing segmented instruction, learner engagement, accessibility, safety, and formative assessment. Learner experiences also revealed challenges related to unstable internet connectivity, shared devices, limited learning space, distraction, and the need for clearer demonstrations and structured guidance. These findings informed the redesign of TeachTok by integrating mirror-mode demonstrations, learner-friendly pacing, safety reminders, private submission procedures, and low-bandwidth accessibility. Expert validation rated the instructional package as highly valid, while learners rated it highly acceptable in terms of perceived usefulness, perceived ease of use, and instructional quality. The study concludes that TeachTok is a feasible and effective Alternative Delivery Mode that supports learning continuity in Grade 5 Physical Fitness during climate-related class suspensions. The study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting equitable and continuous learning and supports SDG 3 (Good Health and Well-Being), SDG 9 (Industry, Innovation and Infrastructure), and SDG 13 (Climate Action) through safe home-based physical activity, innovative digital instruction, and resilient educational delivery. The study contributes to educational sustainability by providing a context-responsive instructional model that strengthens learning continuity, institutional preparedness, and responsible digital learning in disruption-prone communities.